Navigating your US bioscience career into the 2030s. - Peter J Hotez (PLoS Biology)
The coming decade might see major cuts to the United States Government funding for biomedicine and the mainstreaming of pseudoscience. But your biosciences PhD gives you the problem-solving skills to navigate this maelstrom, especially if you maintain flexibility, optimism, and enthusiasm for uncharted paths.